BIOPROSPECÇÃO DE FUNGOS PRODUTORES DE PROTEASES: POTENCIAL PROTEOLÍTICO DE Fusarium oxysporum - Prolo, Thaiane (2015)
The proteolytic enzymes are one of the most important groups of commercial enzymes, representing about 60% of the global market for enzymes. Among the biotechnological applications of proteases, can be mentioned their application in detergents, leather, food, and other industries. The objective of this study was selection fungal that was better protease producers. To this, 73 fungal species were evaluated, 35 yeasts and 38 filamentous fungi. After an initial selection, the effect of various physico-chemical parameters on proteases production by the strain previously selected and subsequently identified as Fusarium oxysporum was investigated, using dog hair in white and black colors as substrates. The experiments were performed using Central composite rotational design applicable to Response Surface Methodology. Proteases produced were biochemically characterized, determining the following parameters: optimum temperature, optimum pH, thermostability, stability at different pH and the influence of ions and substances. Among the evaluated fungal strains, F. oxysporum produced the highest levels of alkaline protease when its was grown in black dog hair. Maximum production levels were achieved when the pH of medium was adjusted to 4.2, substrate concentration was 4.2% and the cultivation time was 8.6 days, corresponding to 72.8 U mL?¹. When it was grown in white dog hair, maximum production levels were obtained in pH of medium adjusted to 6.0, on substrate concentration of 5.0% and cultivation time of 6.5 days, corresponding to 51.84 U mL?¹. Productivity levels obtained employing white and black dog hair as substrates correspond an increase of 14.85 and 7.19 fold, respectively, in relation to the initial activity observed. Both enzymes exhibited desirable properties to be apply in many industries, such as relative thermal stability and action in a wide pH range. Thus, dog hair is a promising residue for alkaline proteases production, in both colors that were tested, due to be a low cost material and generated in large amounts by pet shops throughout the world.